Influence of Domestic Violence on Academic Performance of Primary School Pupils: A Case Study of Kashumba Sub-county, Isingiro District - Vicent Twagirayesu (Uganda Christian University, 2025)
Domestic violence (DV), particularly intimate partner violence (IPV), remains widespread across the globe and has widely established effects on children's learning. This study examined the effect of domestic violence on learning performance among primary school pupils in Kashumba Sub-County, Isingiro District. The study aims were to determine types of domestic violence indicated by pupils, assess learning performance among affected pupils, and suggest ways of mitigating its effects on learning. A quantitative research design and cross-sectional study were employed, where information was gathered from 66 respondents, comprising pupils, teachers, parents, and Child Development Center (CDC) workers. The data were analyzed using SPSS and tabled, charted, frequencies, and percentages. Male respondents accounted for 86.4% while females accounted for 13.6%, with a majority being between the ages of 20–40. The greater majority of learners were in upper primary, 53% accessed government schools, and 74.2% lived in rural settings. The most reported forms of domestic violence were emotional abuse (mean = 4.53), economic hardship (mean = 4.45), and witnessing violence (mean = 4.36). Results showed that domestic violence significantly lowers academic achievement (mean = 4.76), lowers support from parents (mean = 4.52), and leads to truancy (mean = 4.32). Interventions recommended were counseling (mean = 4.73), teacher training (mean = 4.77), school–community partnership (mean = 4.65), financial assistance (mean = 4.45), and public awareness campaigns (mean = 4.27). In essence, domestic violence undermines students' education through absenteeism, poor performance, and low attendance. The study recommends low-cost counseling, teacher training, and improved joint working between schools, local authorities, community organizations, and child protection agencies to deal with the underlying problems and safeguard children's education.
Undergraduate Research